Risks of floating microplastic in the global ocean. (December 2020) - Everaert, G.; De Rijcke, M.; Lonneville, B.; Janssen, C.R.; Backhaus, T.; Mees, J.; van Sebille, E.; Koelmans, A.A.; Catarino, A.I.; Vandegehuchte, M.B.
Abstract: Despite the ubiquitous and persistent presence of microplastic (MP) in marine ecosystems, knowledge of its potential harmful ecological effects is low. In this work, we assessed the risk of floating MP (1 μm–5 mm) to marine ecosystems by comparing ambient concentrations in the global ocean with available ecotoxicity data. The integration of twenty-three species-specific effect threshold concentration data in a species sensitivity distribution yielded a median unacceptable level of 1.21 ∗ 10 5  MP m − ³ (95% CI: 7.99 ∗ 10 3 –1.49 ∗ 10 6  MP m − ³). We found that in 2010 for 0.17% of the surface layer (0–5 m) of the global ocean a threatening risk would occur. By 2050 and 2100, this fraction increases to 0.52% and 1.62%, respectively, according to the worst-case predicted future plastic discharge into the ocean. Our results reveal a spatial and multidecadal variability of MP-related risk at the global ocean surface. For example, we have identified the Mediterranean Sea and the Yellow Sea as hotspots of marine microplastic risks already now and even more pronounced in future decades. Graphical abstract: Image 1 Highlights: Microplastic is widespread in marine ecosystems and knowledge about its risk is low. We integrated ecotoxicity data and compared these with ambient concentrations. To date, 0.17% of the surface of the global ocean is at risk due to microplastic. Under business as usual, this fraction increases to 0.52% (2050) and 1.62% (2100). The Mediterranean Sea and the Yellow Sea are hotspots of marine microplastic risks.